Передача энергии между видами колебаний в сверхразмерном объемном резонаторе; Известия вузов. Физика; Т. 54, № 11(2) - Августинович В. А. Владимир Андреевич; Артеменко С. Н. Сергей Николаевич; Новиков С. А. Сергей Автономович; Юшков Ю. Г. Юрий Георгиевич (2011, 2011)
Заглавие с экрана